Non-fluorescent schemes for single-molecule detection, imaging and spectroscopy - Arroyo, J; Kukura, P (Nature, 2015)
For decades, optical studies of single molecules have relied on fluorescence detection. The availability of alternative approaches for single-molecule interrogation would greatly expand the range of addressable molecules beyond species that are highly emissive and photostable, thus offering new applications in fields other than molecular biophysics and imaging. Here, we discuss the range of recent developments in optical label-free detection and imaging schemes that offer single-molecule sensitivity, with an emphasis on plasmonically enhanced and scattering-based approaches. We highlight the advantages and challenges facing these emerging methodologies and briefly outline their potential future applications.